Update: Topical Antimicrobial Agents for Chronic Wounds. (October 2017) - Sibbald, R. Gary; Elliott, James A.; Verma, Luvneed; Brandon, Alisa; Persaud, Reneeka; Ayello, Elizabeth A.
Abstract : GENERAL PURPOSE: To provide information on the use of topical antimicrobial agents for the treatment of chronic wounds. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant should be better able to: 1. Examine features of wounds and wound healing as well as the purpose of specific antimicrobial agents. 2. Identify potential therapeutic and adverse effects of specific topical antimicrobial agents for the treatment of chronic wounds. ABSTRACT: Bacteria can delay or prevent healing in the surface compartment of a chronic wound or invade the deep and surrounding structures. This article focuses on the superficial compartment and the appropriate use of topical antimicrobial therapies. The authors have reviewed the published evidence for the last 5 years (2012–2017) and extrapolated findings to clinical practice with critical appraisal and synthesis of the recent literature with expert opinion, patient-centered concerns, and healthcare systems perspectives. Summary evidence tables for commonly used topical antimicrobials are included.